146k views
0 votes
Simplify 2•a•b•a•b help needed pleasee

User Wtower
by
6.3k points

1 Answer

6 votes

Answer:


2 a^(2) b^(2)

Explanation:

Step 1: The given expression is 2·a·b·a·b.

Dot represents multiplication.

Step 2: To simplify the expression, arrange like terms into one group

2·a·b·a·b = 2·(a·a)·(b·b)

Step 3: Law of exponents:
x^(m) \cdot x^(n)=x^(m+n)

Using the law of exponents formula, we get

2·(a·a)·(b·b) =
2 a^((1+1)) b^((1+1))

=
2 a^(2) b^(2)

Therefore, 2·(a·a)·(b·b) =
2 a^(2) b^(2)

Hence, the simplified form of 2·(a·a)·(b·b) is
2 a^(2) b^(2).

User Fny
by
5.7k points